Averaging Performance of Capacitance and Time Domain Reflectometry Sensors in Nonuniform Wetted Sand Profiles. Issue 12 (19th December 2014) - van den Elsen, H.G.M.; Ritsema, C.J.; Seeger, M.; Keesstra, S.D.
Abstract : The averaging behavior of two capacitance water content sensors in nonuniform wetted sand samples was assessed and compared with the averaging behavior of a time domain reflectometry (TDR) water content sensor in identical samples. Four different nonuniform wetting situations were assessed. In one of the four experiments, the orientation of the capacitance sensor was altered, while in another the sensitivity along the length of the sensor was tested. For one of the tested sensor types, the overestimation of the volumetric water content (VWC) was 0.034 compared with the value determined by drying, while the corresponding TDR value deviated 0.009. The conclusion is that in a nonuniform wetted soil profile, the capacitance sensors tested weigh the wet parts more heavily than the dry parts, resulting in an overestimation of the average VWC. Therefore we conclude that the capacitance sensors tested are less suitable for applications in situations where both nonuniform wetted profiles are encountered and accurate VWC measurements are required.